Castleman’s disease mimicking lymph node metastases in a young woman with laryngeal cancer - Serkies, Krystyna; Łazar-Poniatowska, Małgorzata; Seredyńska, Joanna; Biernat, Wojciech; Jassem, Jacek (Contemporary Oncology/Współczesna Onkologia, 2016)
Laryngeal cancer occurs rarely in adolescents and young people. Castleman’s disease is a rare lymphoproliferative disorder of uncertain etiopathogenesis and heterogeneous clinicopathological forms. Involved lymph nodes and extranodal lesions in the course of Castleman’s disease may mimic malignant involvement. We report a case of an 18-year-old woman with T2N0M0 laryngeal glottis cancer treated with definitive radiotherapy. During the irradiation, the patient underwent an excision of incidentally discovered left-sided enlarged cervical lymph nodes located outside the irradiated area. Coincidental hyaline vascular type of Castleman’s disease was diagnosed. During six-year follow-up she has been free of cancer relapse and Castleman’s disease symptoms.